Variants of human CLDN9 cause mild to profound hearing loss. Issue 10 (1st August 2021) - Ramzan, Memoona; Philippe, Christophe; Belyantseva, Inna A.; Nakano, Yoko; Fenollar‐Ferrer, Cristina; Tona, Risa; Yousaf, Rizwan; Basheer, Rasheeda; Imtiaz, Ayesha; Faridi, Rabia; Munir, Zunaira; Idrees, Hafiza; et al.
Abstract: Hereditary deafness is clinically and genetically heterogeneous. We investigated deafness segregating as a recessive trait in two families. Audiological examinations revealed an asymmetric mild to profound hearing loss with childhood or adolescent onset. Exome sequencing of probands identified a homozygous c.475G>A;p.(Glu159Lys) variant of CLDN9 (NM_020982.4) in one family and a homozygous c.370_372dupATC;p.(Ile124dup) CLDN9 variant in an affected individual of a second family. Claudin 9 (CLDN9) is an integral membrane protein and constituent of epithelial bicellular tight junctions (TJs) that form semipermeable, paracellular barriers between inner ear perilymphatic and endolymphatic compartments. Computational structural modeling predicts that substitution of a lysine for glutamic acid p.(Glu159Lys) alters one of two cis ‐interactions between CLDN9 protomers. The p.(Ile124dup) variant is predicted to locally misfold CLDN9 and mCherry tagged p.(Ile124dup) CLDN9 is not targeted to the HeLa cell membrane. In situ hybridization shows that mouse Cldn9 expression increases from embryonic to postnatal development and persists in adult inner ears coinciding with prominent CLDN9 immunoreactivity in TJs of epithelia outlining the scala media. Together with the Cldn9 deaf mouse and a homozygous frameshift of CLDN9 previously associated with deafness, the two bi‐allelic variants of CLDN9 described here point to CLDN9 as a bona fide human deafness gene.